2007
DOI: 10.4081/jlimnol.2007.s1.84
|View full text |Cite
|
Sign up to set email alerts
|

Nearctic freshwater tardigrades: a review

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…The vast majority of aquatic samples had no specimens. Streams and rivers in BTNP are relatively slow moving, eutrophic, and laden with sediment, and may be poor habitat for aquatic tardigrades (McFatter et al 2007). Altitudinal variation in BTNP is much less than in mountainous GSMNP.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of aquatic samples had no specimens. Streams and rivers in BTNP are relatively slow moving, eutrophic, and laden with sediment, and may be poor habitat for aquatic tardigrades (McFatter et al 2007). Altitudinal variation in BTNP is much less than in mountainous GSMNP.…”
Section: Discussionmentioning
confidence: 99%
“…Zoogeographical studies on Tardigrada (e.g. McInnes, ; Pilato & Binda, ; McFatter, Meyer & Hinton, ; McInnes & Pugh, ; Meyer & Hinton, ; Meyer, ; Kaczmarek, Michalczyk & McInnes, , , ) are limited by the extent of our knowledge of tardigrade taxonomy and faunistics. Currently, over 1200 species and subspecies of tardigrades have been described (Degma, Bertolani & Guidetti, 2009–2015), with approximately 1000 of these from limno‐terrestrial habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Mathews (1938) compiled a comprehensive list of North American tardigrade species and their distributions, and Marcus (1939) did the same for South America. Nelson (1982) updated Marcus (1939) for aquatic and semi-aquatic species, while McFatter et al (2007) reviewed North American freshwater Tardigrada. Rossi & Claps (1991) and Claps et al (2008) reviewed the tardigrades of Argentina, Assunção (1999) listed the tardigrade species of the state of São Paulo in Brazil, Boeckner et al (2005) provided a list of species found in Canada, Nickel et al (2001) summarized the tardigrades only weak support for such associations.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern holds true when the scale is expanded to include all the Americas. McFatter et al (2007) found that most freshwater studies of North American tardigrades had sampled aquatic vegetation and sediment; in the Americas as a whole most freshwater tardigrades have been collected from these substrates. Guil & Cabrero-Sañudo (2007) remarked on the preponderance of tardigrade studies carried out by scientists from the Palaearctic and Nearctic ecozones; e.g.…”
Section: Introductionmentioning
confidence: 99%